PENINGKATAN PERILAKU KERJA ISLAMI DENGAN BUDAYA ORGANISASI ISLAMI SEBAGAI VARIABEL MODERASI - Diah Ayu Kusumawati (Jurnal Ekonomi dan Bisnis, 2016)
This study aimes to analyze the influence of islamic leadership style, Islamic work ethicand islamic organizations culture to conduct Islamic work behavior in Sultan Agung IslamicUniversity of Semarang. The purpose of this study was to determine the role of organizationalculture islamic to moderate the relationship between leadership style islamic and islamic workethic in Islamic work behavior of the lecturer and staff at the Sultan Agung Islamic Univercity ofSemarang. Data were obtained from 160 respondents to the questionnaire. Data analysis usingSPSS 16 shows that the Islamic leadership style has a significant and positive influence on theislamic work behavior, the islamic work ethic have a significant and positive effect of the reactorislamic work behavior, islamic leadership style has a positive and significant impact on theislamic work ethic, and islamic organizational culture may moderate the relationship betweenislamic leadership style and islamic work ethic against the islamic work behavior of the lecturerand staff at the Sultan Agung Islamic University of Semarang.Keywords: islamic leadership style, islamic work ethic, islamic organizational culture, islamicwork behavior